Knowing from the past – Ingredients and technology of ancient mortar used in Vadakumnathan temple, Tirussur, Kerala, India. (December 2015) - Thirumalini, S.; Ravi, R.; Sekar, S.K.; Nambirajan, M.
Abstract: In the present study, lime mortar samples from the restoration site of Vadakumnathan temple, Kerala, India have been analyzed. Samples from three different locations of the temple such as ancient wall, gopuram and arch have been taken. Traditional methods such as chemical analysis, acid loss analysis and organic test were conducted on mortar samples. Modern instrumental techniques such as electronic particle size distribution, X-ray Diffraction (XRD), scanning electron microscopy coupled with energy dispersive X-ray spectroscopy (SEM/EDX), Thermo Gravimetric Analysis (TGA), Differential Thermal Analysis (DTA) and Infrared Spectroscopy (FT-IR) were employed in the study. The binder used in the mortar is calcium high with 30% of clay mineral. A binder to aggregate ratio in the range of 1:1.5–2.5 has been established from acid loss analysis. Particle of the aggregate are mostly silt in nature, hence nominal sand would have been grinded to reduce the particle size and to induce pozzolanic reaction. The presence of carbohydrate, protein and fats are identified by organic test that are in agreement with FT-IR analysis and TGA. Calcite, aragonite and calcium complexes of silicate and aluminates in form of hydro thermal product namely gyrolite and okenite are present in wall and gopuram samples. The formation of hydrothermal products confirms that the mortar was produced by hot lime technology. In TGA, the decomposition of CaCO3 to CO2 between 600 and 770 °C reveals the transformation of calcite from complex forms of CSH (gyrolite and okenite) and CAH. The presence of degraded products such as syngenite and gypsum in arch sample shows that the lime mortar is in complete deterioration where as mortar remained in good condition in gopuram and wall samples.Texture along with elemental analysis (EDX) confirms the results of chemical analysis. Highlights: Three group of samples namely wall, gopuram and arch from 1300 years old ancient lime mortar plaster from Vadakumnathan temple, India were studied. The binder/aggregate ratio, chemical composition of binders, particle size distribution, role of construction materials used and technology employed for mortar preparation was determined. High strength hydraulic lime with hot lime technology preparation was reported. This work could be extremely useful during the restoration works for better formulation of appropriate repair mortars.